Molecular Mechanisms Driving mRNA Degradation by m6A Modification - Lee, Yujin; Choe, Junho; Park, Ok Hyun; Kim, Yoon Ki (Trends in genetics, 2020)
N6-Methyladenosine (m6A), the most prevalent internal modification associated with eukaryotic mRNAs, influences many steps of mRNA metabolism, including splicing, export, and translation, as well as stability. Recent studies have revealed that m6A-containing mRNAs undergo one of two distinct pathways of rapid degradation: deadenylation via the YT521-B homology (YTH) domain-containing family protein 2 (YTHDF2; an m6A reader protein)–CCR4/NOT (deadenylase) complex or endoribonucleolytic cleavage by the YTHDF2–HRSP12–ribonuclease (RNase) P/mitochondrial RNA-processing (MRP) (endoribonuclease) complex. Some m6A-containing circular RNAs (circRNAs) are also subject to endoribonucleolytic cleavage by YTHDF2–HRSP12–RNase P/MRP. Here, we highlight recent progress on the molecular mechanisms underlying rapid mRNA degradation via m6A and describe our current understanding of the dynamic regulation of m6A-mediated mRNA decay through the crosstalk between m6A (or YTHDF2) and other cellular factors. N6-Methyladenosine (m6A) as an mRNA modification plays multiple roles in various steps/characteristics of mRNA processing and metabolism, such as splicing, export, translation, and stability.YTHDF2 preferentially recognizes m6A and recruits RNA-degrading enzymes or adaptor proteins to trigger rapid degradation of the m6A-containing mRNA.Depending on the presence of HRSP12-binding sites in m6A-containing mRNAs, YTHDF2 elicits one of two RNA decay pathways: deadenylation by the YTHDF2–CCR4/NOT deadenylase complex or endoribonucleolytic cleavage via the YTHDF2–HRSP12–RNase P/MRP complex.The stability of m6A-containing mRNAs is regulated by the dynamic crosstalk between m6A and other cellular factors, such as RNA-binding proteins, RNA structures, and/or other types of modification.